2015
DOI: 10.1371/journal.pone.0140028
|View full text |Cite
|
Sign up to set email alerts
|

The More the Better? A Comparison of the Information Sources Used by the Public during Two Infectious Disease Outbreaks

Abstract: Recent infectious disease outbreaks have resulted in renewed recognition of the importance of risk communication planning and execution to public health control strategies. Key to these efforts is public access to information that is understandable, reliable and meets their needs for informed decision-making on protective health behaviours. Learning from the trends in sources used in previous outbreaks will enable improvements in information access in future outbreaks. Two separate random-digit dialled telepho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 29 publications
0
49
1
Order By: Relevance
“…Six anonymous network sampling surveys (9)(10)(11)(12)(13)(14) were conducted during the COVID-19 outbreak, and the other 18 surveys (15-32) were for SARS and MERS. Nine studies (11,13,15,16,18,20,22,43,44) mentioned the channels from where people obtained health education information. We also found out three studies about health education campaigns (33)(34)(35).…”
Section: Study Resultsmentioning
confidence: 99%
“…Six anonymous network sampling surveys (9)(10)(11)(12)(13)(14) were conducted during the COVID-19 outbreak, and the other 18 surveys (15-32) were for SARS and MERS. Nine studies (11,13,15,16,18,20,22,43,44) mentioned the channels from where people obtained health education information. We also found out three studies about health education campaigns (33)(34)(35).…”
Section: Study Resultsmentioning
confidence: 99%
“…Newspapers are one form of media that southern populations (Jardine et al 2015) and Arctic residents use to seek information about health risks (Boyd et al 2011). For example, a study of residents in two communities in the Northwest Territories found that over half of participants used newspapers to find information about health risks (Boyd et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how the public gathers information on infectious diseases, and what media channels are preferred to deliver customized messages before an outbreak, equips the government with useful information for risk communication planning [21,22]. Credible and timely message delivery through appropriate media channels is necessary to ensure the public gets accurate information on emerging infectious diseases to make informed decisions on protective health behaviors [23,24]. Studies have also shown that inconsistent and untargeted risk communication messages may result in gaps in health-related knowledge and eventually, health outcomes [25][26][27].…”
Section: Introductionmentioning
confidence: 99%